(untitled) (Global Media Journal - German Edition, 2018)
Using structuration theory, assuming that every government has a stake in steering pub-lic communication and comparing 46 nation-states, this paper explores the major principles that can be used to explain different mass media structures around the globe. The study draws on exten-sive documentary analysis and includes more than 150 expert interviews. It shows that media free-dom and journalists’ autonomy depend on not only the particular governmental system, the consti-tution, journalism education, and the existence of commercial media but also, to a significant ex-tent, on economic realities, the tradition of press freedom, and various other factors that are histor-ical, religious, and/or geographic. The tool to do so is a mass media system typology based on two dimensions: formal expectations and the state’s influence.